Cancer vaccines - Savelyeva, Natalia (Lecturer in Cancer Immunology); Ottensmeier, Christian (Springer, 2017)
This volume focuses on the laboratory and clinical experience with targeting viral onco-antigens, while also reviewing the approaches to targeting self-cancer antigens in cancers of non-viral origin, where self-tolerance has been a challenge. It emphasizes the importance of selecting the right vaccine platform to induce a successful immune response against cancer antigens. In addition, the volume discusses the advances made with genetic vaccines, including recent advances with DNA vaccines and the rapid transition of mRNA vaccines from the laboratory to bedside. The new avenues opening up for cancer immunotherapy underline the importance of combinational approaches using cancer vaccines with costimulatory antibodies, which may dramatically improve cancer treatment. This book is intended for all translational researchers and clinicians who aspire to develop novel vaccination approaches for cancer patients with unmet clinical needs.- Resumé vydavatel
Keywords: maligní nádorová onemocnění; očkování; cancer; vaccination; elektronické knihy; sborníky; electronic books; papers of several authors